Herbal-based tea bag reduces SARS-CoV-2 variant symptoms and infection duration via microRNA regulation: Clinical and mechanistic insights - Kai-Wei Chang; Yen-Ying Kung; Shu-Ling Fu; Ju-Fang Liu; Kun-Chang Wu; Tzu-Hau Shi; Yu-Han Luo; Chao-Hsiung Lin; Jih-Jung Chen; Yueh-Hsin Ping; Tung-Hu Tsai; Muh-Hwa Yang (Journal of Functional Foods)
Objective: MicroRNAs (RNA) are crucial in combating SARS-CoV-2; Some traditional Chinese herbal formulas (CHF) have shown potential against the original SARS-CoV-2 strain but no research explores CHF’s role in regulating microRNAs to combat the virus. This study aimed to investigate whether a herbal-based tea bag, Zheng-Yi-Fang (ZYF), from the modified combination of Jie-Geng-Tang (桔梗湯) and Huopu-Xia-Ling-Tang (藿朴夏苓湯) with Houttuynia cordata and Scutellaria baicalensis, can alleviate mild SARS-CoV-2 variant symptoms through microRNA regulation. Methods: Patients with SARS-CoV-2 were recruited via telemedicine services at Taipei Veterans General Hospital from August to December 2022. Participants were randomly assigned to the ZYF group or a control group receiving standard Western medicines for symptom relief. Efficacy was evaluated by clinical symptom scores and the duration for positive antigen results to turn negative. Additional assays assessed spike protein fusion, viral main protease (Mpro) activity, IL-6/IL-8 secretion, and miRNA induction. Results: ZYF demonstrated efficacy in alleviating the symptoms of SARS-CoV-2 variants infection in the nasal, throat, upper respiratory areas, and gastrointestinal tract, while reducing the time required for positive antigen results to turn negative. ZYF inhibited spike protein fusion, regulated miRNA-98 to decrease ACE2 and TMPRSS2 expression, and inhibited Mpro activity. ZYF also modulated miRNA-146a expression, reducing IL-6/IL-8 secretion. Conclusions: Our findings suggest that the herbal-based tea bag offers a novel antiviral approach against SARS-CoV-2 variants by modulating miRNAs, reducing viral entry and IL-6/IL-8 secretion, and inhibiting Mpro activity.